THE EFFECT OF PHOSPHATE FERTILIZER DOSAGE ON THE GROWTH AND YIELD OF TOMATO (Lycopersicum esculentum Mill) ON PEAT SOIL - herlina dian; putu dupa bandem; siti hadijah (Jurnal Sains Pertanian Equator, 2019)
This study aimed to obtain the best phosphate fertilizer dosage on the growth and yield of tomato on peat soil.  The experient was conducted from 15th November 2018 – 31st January 2019 in the experimental garden of the Faculty of Agriculture, Tanjungpura University, Pontianak.  This study used a completely randomized design (CRD) method with one factor SP-36 phosphate fertilizer treatment consisting of 5 treatment levels, and 5 replications and each treatment consisted of 4 plant samples, so that there were 100 plants.  The treatment in question is: p1 = 1.5 g / polybag equivalent to 100 kg / ha, p2 = 2.3 g / polybag equivalent to 150 kg / ha, p3 = 3 g / polybag equivalent to 200 kg / ha, p4 = 3  , 8 g / polybag is equivalent to 250 kg / ha and p5 = 4.5 g / polybag is equivalent to 300 kg / ha.  The variables observed in this study were plant height (cm), root volume (cm3), plant dry weight (g), number of fruits per plant (fruit), weight per fruit (g), weight of fruit per plant (g).  The results showed that the aplication of various SP-36 phosphate fertilizers gave the same result on all observation variables.  However, it has a significant effect on root volume.  The dosage of Phosphate SP-36 fertilizer has a better effect of 3 g / polybag equivalent to 200 kg / ha. Keyword : SP-36 Phosphate Fertilizer, Tomato, Peat Soil